Liquid biofuels from food crops in transportation – A balance sheet of outcomes. (May 2021) - Barr, Meredith R.; Volpe, Roberto; Kandiyoti, Rafael
Highlights: The production and utilization of biofuels from food crops have been reviewed. The energy for making biofuels has been compared with that released by combustion. The use of crops for fuel on the cost of grain and arable land has been examined. The scale of biofuels production is small compared to the resources mobilized. Biofuels policies have created lobbies more invested in profit than the environment. Abstract: The production and utilization of biofuels from food crops have been reviewed. Developments in Brazil, the United States, the European Union and China have been assessed in relation to the aims of biofuels policies, their costs and outcomes. The energy input for making biofuels has been compared with energy released during their combustion. The effect of using crops for fuel on the cost of grain for food and of arable land have been examined. There is evidence that current international policies have caused environmental degradation greater than the fossil fuels they were purported to replace. However, policy choices are difficult to reverse. Despite vast effort and expense, the actual scale of biofuels production is small compared to the resources that have been mobilized. As these processes have evolved, new groups of commercial interests have coalesced internationally, to take advantage of the subsidies with little recognizable benefit to the environment.